Gut microbiota modulates alcohol withdrawal-induced anxiety in mice. (1st May 2018) - Xiao, Hui-wen; Ge, Chang; Feng, Guo-xing; Li, Yuan; Luo, Dan; Dong, Jia-li; Li, Hang; Wang, Haichao; Cui, Ming; Fan, Sai-jun
Highlights: Oral alcohol consumption educated gut microbiota. Oral alcohol consumption altered gut microbiota composition but not abundance. Enteric bacteria participated in the formation of alcohol withdrawal-induced anxiety. Gut microbes might be employed as therapeutic targets for alcohol abuse associated symptom. Abstract: Excessive alcohol consumption remains a major public health problem that affects millions of people worldwide. Accumulative experimental evidence has suggested an important involvement of gut microbiota in the modulation of host's immunological and neurological functions. However, it is previously unknown whether enteric microbiota is implicated in the formation of alcohol withdrawal-induced anxiety. Using a murine model of chronic alcoholism and withdrawal, we examined the impact of alcohol consumption on the possible alterations of gut microbiota as well as alcohol withdrawal-induced anxiety and behavior changes. The 16S rRNA sequencing revealed that alcohol consumption did not alter the abundance of bacteria, but markedly changed the composition of gut microbiota. Moreover, the transplantation of enteric microbes from alcohol-fed mice to normal healthy controls remarkably shaped the composition of gut bacteria, and elicited behavioral signs of alcohol withdrawal-induced anxiety. Using quantitative real-time polymerase chain reaction, we further confirmed that the expression of genes implicated in alcohol addiction, BDNF, CRHR1 and OPRM1, was also altered by transplantation of gut microbes from alcohol-exposed donors. Collectively, our findings suggested a possibility that the alterations of gut microbiota composition might contribute to the development of alcohol withdrawal-induced anxiety, and reveal potentially new etiologies for treating alcohol addiction.